2020
DOI: 10.1186/s12894-020-00628-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of systemic inflammatory factors NLR, LMR, PLR and LDH in penile cancer

Abstract: Background Penile squamous cell carcinoma (PSCC) represents an important public health problem for developing countries. The major prognostic factors in PSCC are pathological subtype, perineural invasion, lymphovascular invasion, depth of invasion and grade, which are hard to obtain precisely before the operation. Besides, micro-metastases will be detected in about 30% of intermediate-risk patients with clinically non-palpable inguinal lymph nodes after inguinal lymph node dissection (ILND). It means approxima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 19 publications
0
23
3
Order By: Relevance
“…The influence of inflammation and immunonutrition on the prognosis of cancer patients is the basis of many studies, and there is an important relationship between malnutrition and increased inflammation and the poor prognosis of cancer patients ( 34 , 35 ). Currently, tools to objectively assess nutritional status are poorly studied in cancer patients, while PNI, NLR, and CONUT scores can predict the prognosis of cancer patients, while they are objective and readily available ( 25 , 36 ). Controlling nutritional status (CONUT) score is a relatively new immuno-nutritional biomarker, which has the advantages of simplicity, low cost and comprehensibility.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of inflammation and immunonutrition on the prognosis of cancer patients is the basis of many studies, and there is an important relationship between malnutrition and increased inflammation and the poor prognosis of cancer patients ( 34 , 35 ). Currently, tools to objectively assess nutritional status are poorly studied in cancer patients, while PNI, NLR, and CONUT scores can predict the prognosis of cancer patients, while they are objective and readily available ( 25 , 36 ). Controlling nutritional status (CONUT) score is a relatively new immuno-nutritional biomarker, which has the advantages of simplicity, low cost and comprehensibility.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, significant poor prognosticator in patients with penile cancer include lymph node positivity ( 27 ), metastatic nodes≥ 4 ( 28 ), AJCC stage ≥ III disease ( 26 ), pathologic stage of the primary tumor ( 29 ), histologic grade<G1 ( 30 , 31 ), a tumor thickness≥ 5 mm ( 32 ), vertical growth pattern ( 33 ), age<53, Lactate Dehydrogenase (LDH)<188.5 U/L and Platelet-lymphocyte Ratio (PLR)<133.5 ( 34 ), p53 positivity ( 31 ), Human papillomavirus infection ( 35 ). However, there are few studies on the prognosis of penile cancer at the gene level, so our study also studied the gene types of prognostic factors later.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an increasing number of studies have demonstrated the value of inflammatory response biomarkers as predictive markers for prognosis in cancers. It has been shown that the neutrophil-tolymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and systemic immune inflammation index (SII) can predict the prognosis in various types of cancers (7)(8)(9). The systemic inflammation response index (SIRI) is a new systemic inflammatory response biomarker based on peripheral blood cells counts, and it was demonstrated to be effective in predicting the prognosis of esophagogastric junction adenocarcinoma (10), esophageal cancer (11) and cervical cancer (12).…”
Section: Introductionmentioning
confidence: 99%